Penerapan metode weighted aggregated sum product assesment (waspas) dalam sistem pendukung keputusan untuk menentukan penerima bantuan program indonesia pintar (PIP) (studi kasus : SMK Islam Terpadu Minnatul Huda Plered Purwakarta) - Suciaty, Nenda Putri; Irmayanti, Dede; Alam, Syariful (Universitas Mercu Buana, 2024)
The Smart Indonesia Program (PIP) is an assistance program from the government for school-age children whose parents are less able to provide cash assistance as indicated by the existence of a Smart Indonesia Card (KIP). However, this program at Minnatul Huda Integrated Islamic Vocational School is still felt to be not on target in determining potential beneficiaries because it is not only from poor families who receive it and this causes injustice to students who meet the criteria for receiving PIP assistance. By making purchases using a decision support system, it is hoped that it will help reduce inaccuracies in selecting prospective beneficiaries. The Decision Support System in this study applies the Waterfall system development method and the appropriate Weighted Aggregated Sum Product Assessment (WASPAS) method to calculate the ranking of potential recipients of PIP assistance and uses the Rank Order Centrooid (ROC) method for weighting each rank according to its importance. This system uses UML (Unified Modeling Language) modeling, namely Use Case Diagrams, Use Case Scenario Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams, the programming language uses PHP, CodeIgniter Framework, and MySQL database. The features available in the system include the user can only see the final result data and print the final result, while the admin can manage criteria data, sub-criteria, alternatives, and assessments, and can view calculations and final results, the admin can also print the final results and manage user data and profile data. The results of the calculation process obtained alternative values that have the highest to lowest values as determinants of PIP assistance recipients. The research conducted resulted in the Agisna Billah Nurzaman Alternative as the Alternative with the highest score and the Iyah Saadah Alternative as the Alternative with the lowest score. Testing the system using black box testing.